Applications of the session rating of perceived exertion system in professional Rugby Union. - Comyns, T.; Flanagan, E. P. (Strength and Conditioning Journal, 2013)
This article instructs strength and conditioning practitioners in the use of the session rating of perceived exertion system of training load monitoring in the context of the professional Rugby Union environment. An explanation of the system and the research underpinning its validity and reliability is presented. The use of the system to manage squad and individual player training plans within weeks and across weeks is detailed. Common errors that can be encountered when using the system within professional Rugby Union are addressed.